Reduced Immunity Regulator MAVS Contributes to Non-Hypertrophic Cardiac Dysfunction by Disturbing Energy Metabolism and Mitochondrial Homeostasis - Wang, Qian; Sun, Zhenzhen; Cao, Shihan; Lin, Xiuli; Wu, Mengying; Li, Yuanyuan; Yin, Jie; Zhou, Wei; Huang, Songming; Zhang, Aihua; Zhang, Yue; Xia, Weiwei; et al. (Frontiers in Immunology, 2022)
Cardiac dysfunction is manifested as decline of cardiac systolic function, and multiple cardiovascular diseases (CVDs) can develop cardiac insufficiency. Mitochondrial antiviral signaling (MAVS) is known as an innate immune regulator involved in viral infectious diseases and autoimmune diseases, whereas its role in the heart remains obscure. The alteration of MAVS was analyzed in animal models with non-hypertrophic and hypertrophic cardiac dysfunction. Then, MAVS-deficient mice were generated to examine the heart function, mitochondrial status and energy metabolism. In vitro, CRISPR/Cas9-based gene editing was used to delete MAVS in H9C2 cell lines and the phenotypes of mitochondria and energy metabolism were evaluated. Here we observed reduced MAVS expression in cardiac tissue from several non-hypertrophic cardiac dysfunction models, contrasting to the enhanced MAVS in hypertrophic heart. Furthermore, we examined the heart function in mice with partial or total MAVS deficiency and found spontaneously developed cardiac pump dysfunction and cardiac dilation as assessed by echocardiography parameters. Metabonomic results suggested MAVS deletion probably promoted cardiac dysfunction by disturbing energy metabolism, especially lipid metabolism. Disordered and mitochondrial homeostasis induced by mitochondrial oxidative stress and mitophagy impairment also advanced the progression of cardiac dysfunction of mice without MAVS. Knockout of MAVS using CRISPR/Cas9 in cardiomyocytes damaged mitochondrial structure and function, as well as increased mitochondrial ROS production. Therefore, reduced MAVS contributed to the pathogenesis of non-hypertrophic cardiac dysfunction, which reveals a link between a key regulator of immunity (MAVS) and heart function.